Co-creation with research participants to inform the design of electronic informed consent. (June 2022) - De Sutter, Evelien; Geerts, David; Borry, Pascal; Coteur, Kristien; Bamps, Dorien; Marynissen, Heleen; Ampe, Els; Geenens, Els; Depré, Marleen; Huys, Isabelle
Objective: This study aimed to provide recommendations for a personalized electronic informed consent interface that is adapted to research participants' needs and could enable a longitudinal interaction between the participants and the research team. Methods: The co-creation process consisted of three co-creation workshops, one focus group discussion, and four semi-structured interviews. In total, 24 participants, who had taken part in four disparate clinical studies in Belgium, were involved. Descriptive statistics and qualitative content analysis were applied to analyze the survey data and audio recordings. Results: Varying perceptions on the type and amount of information described in an informed consent form were reported. Other findings were related to the structure and presentation of information, setting preferences for data sharing, and electronically signing new informed consent versions. Regarding the long-term interaction, most of the participants wanted to receive progress updates, including the results, of the study in which they had taken part. They proposed to receive a notification, preferably via email, in case new information is made available on the electronic informed consent interface. Conclusions: To optimally support the design of an electronic informed consent interface, it is key to understand the research participants' needs. Study findings suggest that an electronic informed consent interface may be a promising technological application to interactively provide study-related information and to keep participants informed during and after the clinical study.